Spiritual Education through Ziarah Tradition in Syaikh Syamsuddin Al-Wasil Kediri - M. Al-Qodhi Abi Saidil Mahzumi; A. Jauhar Fuad (UIN Maulana Malik Ibrahim Malang, 2019)
This paper aims to examine the development of spirituality that is traversed through the grave pilgrimage tradition by utilizing symbolic interactionist theory, religious and cultural theory, and spiritual intelligence theory. This study wanted to reveal the process and impact of a person’s spiritual change after carrying out the tradition of pilgrimage in the Tomb of Shaykh Syamsuddin al-Wasil, Kediri city. The results of this study show that first, spiritual process of pilgrims starts from the reason for making the tomb of Shaykh Syamsuddin Al-Wasil, Kediri city as an object of spiritual education, namely a media reminder for pilgrims, efforts to approach pilgrims to Allah, and as a place of prayer. The spiritual process itself is divided into three stages, namely; (1) pre-pilgrimage by purifying with ablution, (2) the stage of pilgrimage begins with tawasul on special people, reading the Qur’an, reading tahlil and finally reading the do’a, (3) after the pilgrimage by doing shodaqoh. Second, in terms of spiritual changes in the pilgrim’s self, namely; (1) inner changes such as calmness of heart and feeling holy heart, (2) changes in the end like feeling in living life more diligently and zealously, feeling lazy disappears, and pilgrims can control emotions.Tulisan ini bertujuan untuk mengkaji pengembangan spiritualitas yang dilalui dengan cara tradisi ziarah kubur dengan memanfaatkan teori interaksionis simbolis, teori agama dan budaya, serta teori kecerdasan spiritual. Penelitian ini mengungkap proses dan dampak perubahan spiritual sesorang setelah melakukan tradisi ziarah di Makam Syaikh Syamsuddin al-Wasil kota Kediri. Hasil penelitian ini menemukan bahwa; pertama proses spiritual peziarah bermula dari alasan menjadikan makam Syaikh Syamsuddin Al-Wasil Kota Kediri sebagai objek pendidikan spiritual yakni, media pengingat bagi peziarah, upaya mendekatan peziarah pada Allah, dan sebagai tempat berdo’a. Proses spiritual sendiri dibagi menjadi tiga tahap yakni; (1) pra ziarah dengan melakukan penyucian dengan berwudhu, (2) tahap ziarah dimulai dengan bertawasul pada orang-orang khusus, membaca al-Qur’an, membaca tahlil dan terakhir membaca do’a, (3) pasca ziarah dengan melakukan shodaqoh. Kedua, segi perubahan spiritual yang terjadi pada diri peziarah yakni; (1) perubahan secara batin seperti ketenangan hati dan merasa hati menjadi bersih, (2) perubahan secara dhohir seperti merasa dalam menjalani hidup semakin rajin dan bersemangat, rasa malas menghilang, dan peziarah dapat mengontrol emosi.